A rollercoaster first year as an RVN… after a rollercoaster route in!. Issue 11 (15th October 2021) - Curtis, Sally
Abstract: Following on from my career change story where I described my move from a creative career to a Student Veterinary Nurse (SVN), comes the opportunity to reflect on my first year as a Registered Veterinary Nurse (RVN) since qualifying in April 2019. From first opinion practice, a location change, and then onwards to referral hospital world, how has so much happened within twelve months of putting on "that" badge?